Facile synthesis of three-dimensionally ordered macroporous silicon-doped La0.8K0.2CoO3 perovskite catalysts for soot combustion. Issue 21 (17th August 2016) - Feng, Nengjie; Chen, Chong; Meng, Jie; Wu, Yang; Liu, Geng; Wang, Lei; Wan, Hui; Guan, Guofeng
Abstract : Three-dimensionally ordered macroporous (3DOM) silicon-doped La0.8 K0.2 CoO3 perovskite catalysts were successfully prepared by a colloidal crystal templating method. The catalysts showed a well-ordered macroporous structure and exhibited high activity for soot removal. Abstract : Three-dimensionally ordered macroporous (3DOM) silicon-doped La0.8 K0.2 CoO3 perovskite catalysts were prepared by a colloidal crystal templating method. The as-prepared samples were characterized by XRD, FT-IR, FESEM, N2 adsorption–desorption, XRF, XPS and H2 -TPR techniques to investigate the physical–chemical properties of the catalysts. The silica sol added into the perovskite precursor solution could be solidified at a relatively low temperature, which prevented the 3DOM structure from collapsing during calcination. Meanwhile, the specific surface areas and redox abilities of the catalysts could also be enhanced. The catalytic performance for soot combustion was evaluated in a temperature programmed oxidation device using NO/O2 as an oxidant. Among all the as-prepared catalysts, 3DOM La0.8 K0.2 CoO3 perovskite doped with 5.89 wt% Si (3DOM LKC-S2) exhibited the best catalytic performance for soot removal.